Optimization of hole spacing for cut-top blasting based on new hole-sealing technology - Wang, Chao; Yin, Zhiqiang; Ma, Yankun; Chen, Deren; Wang, Dengke; Zhao, Aohan (Frontiers in Earth Science, 2023)
In order to solve the problem of stress concentration on the roof of the mining trench, reduce the risk of sudden collapse of the roof overburden and disturbance, improve the control effect of the surrounding rock of the roof cutting and retaining roadway, and reduce the construction cost of mining tunnels, a new type of pouch sealing technology has been developed. By using on-site testing methods, the optimal sealing material ratio was optimized, and the crack propagation law and roof cutting effect of the 11503 W working face in Zhaizhen Coal Mine, Shandong Province were studied under hole spacing of 0.7, 1.0, and 1.1 meters and different sealing methods. The results show that using 1.5 m single pouch sealing technology in the blasting test, when the water cement ratio of the sealing material is 1:1, the required sealing strength and sealing temperature can be achieved, and there will be no punching phenomenon. When the spacing between holes is 1 m, the blasting effect is optimal, with a single hole effectively reaching a cutting seam length of about 0.5 m. There are obvious through cracks in the cave, with a total length of about 7 meters. After using the new pouch sealing technology for blasting, the displacement and bottom drum volume on both sides of the tunnel are lower than those of the traditional yellow mud sealing method, and the bottom drum volume is reduced by 37% and 53%, respectively. Based on comprehensive theoretical analysis and on-site experiments, the optimal hole spacing is determined to be 1 m, and the pouch sealing effect is good.